DAMPAK AKREDITASI DAN SERTIFIKASI DALAM PEMBINAAN LEMBAGA PENDIDIKAN ISLAM - Hayatun Nufus; Nurul Masruni; Dhiya Aulia; Suriagiri; M. Nur Effendi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to analyze the impact of accreditation and certification on the development of Islamic educational institutions, especially in improving institutional quality and teacher professionalism. This research uses a literature study method by collecting data from books, scientific journals, and previous relevant studies. The data were analyzed descriptively through reviewing and interpreting theories and research findings related to accreditation, certification, and the quality of Islamic education. The results show that accreditation plays an important role in improving institutional management, curriculum standardization, and learning processes that are more organized, active, and student-centered. In addition, teacher certification has a positive impact on improving pedagogical competence, professionalism, discipline, and the quality of classroom learning. Certified teachers tend to be better at planning and carrying out effective learning activities and using more varied and innovative teaching methods. However, the implementation of accreditation and certification still faces several challenges, such as limited facilities, lack of continuous training, and low use of technology. Therefore, the success of accreditation and certification in improving the quality of Islamic education requires institutional commitment, teacher motivation, and continuous guidance and evaluation.